2022
DOI: 10.1186/s12576-022-00854-0
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture improves cognitive impairment in diabetic cognitive dysfunction rats by regulating the mitochondrial autophagy pathway

Abstract: Background Diabetes-associated cognitive dysfunction has become a major public health concern. However, the mechanisms driving this disease are elusive. Herein, we explored how electroacupuncture improves learning and memory function in diabetic rats. Methods The diabetic model was established by intraperitoneal injection of streptozotocin (STZ) in adult Sprague–Dawley rats. Rats were fed on high-fat and high-sugar diets. Learning and memory functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Currently, there is no effective drug to treat diabetes-related cognitive impairment. Electroacupuncture shows good therapeutic effect on cognitive impairment ( 26 ). Our results reveal that electroacupuncture can improve the learning and memory function of diabetic mice by reducing ERS, inhibiting JNK expression and removing Aβ and Tau from hippocampal neuron cells.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no effective drug to treat diabetes-related cognitive impairment. Electroacupuncture shows good therapeutic effect on cognitive impairment ( 26 ). Our results reveal that electroacupuncture can improve the learning and memory function of diabetic mice by reducing ERS, inhibiting JNK expression and removing Aβ and Tau from hippocampal neuron cells.…”
Section: Discussionmentioning
confidence: 99%
“… 47 Mitophagy and structural changes of mitochondria are the main causes of neuronal dysfunction. 48 Ge et al 49 established a diabetic model of adult SD rats by using streptozotocin (STZ) have shown that electroacupuncture promotes mitophagy and improves the learning and memory function of rats by increasing the expression of Disrupted-in-Schizophrenia 1 (DISC1). The down-regulation of DISC1 leads to mitochondrial dysfunction and synaptic plasticity, resulting in cognitive impairment.…”
Section: Regulate Mitophagymentioning
confidence: 99%
“…Autophagy dysfunction is one of the major pathological hallmarks of neurodegenerative disease-associated CI [ 20 ]. Interestingly, studies demonstrated that enhanced mitophagy in damaged hippocampal neurons is conducive to improving cognitive dysfunction in rats [ 21 ]. In this context, the effect of NTRK1 on mitophagy in neurons has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%